Social Competences of Enterprise Employees on The Labor Market During Pandemic Covid – 19 - Bartosz SYLWESTRZAK; Stanislawa OSTASIEWICZ (Communications of International Proceedings, 2021)
Changes occuring in the social behaviour patterns of citizens in both professional and private relationships as a result of isolation during the Covid-19 pandemic are dynamic and has far-reaching effects. Additionally, this phenomenon is fostered by technological progress and the availability of devices that support the virtual world. This affects the behaviour of staff in work relationships and the demands of employers when looking for new employees.  Opinions of experts and employers in Poland emphasize the importance of social competence in the effective professional activity of employees, especially in relation to the restrictions introduced due to the Covid-19 pandemic; successive lockdowns and isolation have resulted in significant gaps in the area of this competence.
Keywords: employee’s competences; labor market; Covid – 19.